The impact of multi-enzyme fortification on growth performance, intestinal morphology, nutrient digestibility, and meat quality of broiler chickens fed a standard or low-density diet - Attia, Youssef A.; Al-Khalaifah, Hanan S.; Alqhtani, Abdulmohsen H.; Abd El-Hamid, Hatem S.; Alyileili, Salem R.; El-Hamid, Abd El-Hamid E. Abd; Bovera, Fulvia; El-Shafey, Ali A. (Frontiers in Veterinary Science, 2022)
This research aimed to study the impact of supplementation of three multi-enzymes levels (0, 0.1, and 0.2% of feed) and two levels of dietary treatments [standard diet (SD) vs. low-density diet, (LDD)] on growth performance, carcass traits, digestibility, and meat quality of broilers from 1-38 d of age. Two hundred and sixteen d 1 old Arbor Acres broiler chicks were randomly distributed on a factorial design (2 × 3) with six dietary treatments, each with six replicates and six chickens in a replicate. The results showed that the LDD significantly reduced body weight gain by 5.0%, compared to the SD. Multi-enzymes significantly improved body weight gain and production index (PI) relative to the SD. The feed conversion ratio was significantly enhanced with increased multi-enzymes from 1-21 d. A significant relation between multi-enzymes concentration and type of dietary treatment was shown in body weight gain and feed conversion ratio from 1-21 d of age. Nitrogen-free extract digestibility was significantly increased by using the SD diet compared to the LDD. Multi-enzymes supplementation improved the digestibility of dry matter, crude protein, crude fiber, and nitrogen-free extract in LDD. There was a significant relationship between multi-enzymes concentration and type of dietary treatment on pancreas, liver, and intestinal length percentages. Meat dry matter concentration was significantly higher in the LDD group than those in the SD group. Low-density diet significantly reduced the total revenue compared to the SD, whereas broilers fed SD recorded significantly higher total revenue and economic efficiency than LDD. Low-density diet significantly increased economic efficiency compared to SD. Multi-enzymes significantly increased the total revenue, net revenue, and economic efficiency than the standard set. In conclusion, using multi-enzymes in broilers diet improved body weight gain. LDD with multi-enzymes showed enhanced body weight gain than SD without multi-enzymes.